ADOPTION LEVEL OF SHEEP HUSBANDRY PRACTICES IN BHILWARA DISTRICT OF RAJASTHAN - YADAV, C.M. (Indian Journal of Animal Production and Management, 2017)
ABSTRACTThe study was conducted in Bhilwara district by incorporating a total 120 farmersselected from adopted and non-adopted area. Fifteen technologies in sheep husbandrypractices were identified to study the adoption level among farmers - selection and purchaseof quality sheep (58.33 %), provision of shelter for animals (46.67 %), feeding of colostrumsto new born lamb (100 %), period of grazing (100%), feeding of crushed grain (58.33%),feeding of tree leaves in summer (70 %), deworming (73.33%), vaccination of sheep (60%)and marketing of ram lamb at 6 months of age (83.33) were adopted by majority of theparticipant farmers. In the case of farmers from non-adopted area, period of grazing (100%),feeding of colostrums to new born lamb (70 %) and feeding of tree leaves (50 %) were thepractices adopted by farmers, while majority of them were non-adopters to the remainingpractices in sheep husbandry. Majority of the adopted area expressed that the reason fornon-adoption of recommended practices were lack of knowledge, lack of time and lack ofveterinary services and non-availability of inputs.Key words : Adopted, Non-adopted area, Sheep, Husbandry practices, KVK, Rajasthan